Structural and physiological studies of the Escherichia coli histidine operon inserted into plasmid vectors. - Bruni, C B (1980)
A fragment of deoxyribonucleic acid 5,300 base paris long and containing the promoter-proximal portion of the histidine operon of Escherichia coli K-12, has been cloned in plasmid pBR313 (plasmids pCB2 and pCB3). Restriction mapping, partial nucleotide sequencing, and studies on functional expression in vivo and on protein synthesis in minicells have shown that the fragment contains the regulatory region of the operon, the hisG, hisD genes, and part of the hisC gene. Another plasmid (pCB5) contained the hisG gene and part of the hisD gene. Expression of the hisG gene in the latter plasmid was under control of the tetracycline promoter of the pBR313 plasmid. The in vivo expression of the two groups of plasmids described above, as well as their effect on the expression of the histidine genes not carried by the plasmids but present on the host chromosome, has been studied. The presence of multiple copies of pCB2 or pCB3, but not of pCB5, prevented derepression of the chromosomal histidine operon. Possible interpretations of this phenomenon are discussed.